AUTHORIAL PRESENCE IN ENGLISH RESEARCH ARTICLES BY NATIVE AND NON-NATIVE ENGLISH SCHOLARS - Januarto, Adelia; Hardjanto, Tofan Dwi (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2020)
In this corpus-based study, we address the issue of authorial presence in English research articles (RAs) by native and non-native English scholars in the field of second language writing. Our purposes are to compare the frequencies of authorial presence and to examine discourse functions of authorial presence in the native and non-native English scholars? RAs. To achieve these purposes, 48 RAs were collected from two Scopus-indexed journals, namely Journal of Second Language Writing and Assessing Writing. Overall, our finding suggests that native and non-native English scholars are different in terms of degree of visibility in which native English scholars are more visible than their non-native counterparts in their RAs. Furthermore, our functional analysis of authorial presence indicates that both native and non-native English scholars tend to use authorial presence more for the same purposes, i.e. to describe the research procedures and show the organizations of the texts. The similarity between the two groups may be caused by the international publishing context and the disciplinary writing practice in second language writing. In addition, these findings may be invaluable to material designs in English writing, especially in Indonesia, to assist students as novice writers to consider their explicit presence in their RAs.